Effect of The Drying Time of Unhulled Rice on The Rice Quality of Variety Inpari-7 - I. Ismail; Muhammad Akhsan Akib; Murni Mahmud (Agrotech Journal, 2022)
High rice consumption necessitates an improvement in rice quality. Rice quality issues can result from pest attacks, unhulled rice transportation, harvesting, and drying. An alternative is to use a drier to enhance the quality of rice. Therefore, research to evaluate the quality of rice dried in a dryer with various drying times is required. The Rice Milling Unit, Harapan Village Unit Cooperative (VUC), Tiroang Sub-District, Pinrang District, located at coordinates 3O48'41"S and 119O42'5E, was the site of this study. This study was set up using a Randomized Block Design (RBD), with the treatment of unhulled rice drying duration, namely drying according to farmers' customs (A0), drying for 10 hours (A1), and drying for 12 hours (A2) using a dryer at an average temperature of 65OC. The results showed that a good percentage of whole grains, broken grains, groats grains, whitewash grains, yellow grains, red grains, unhulled grains, and foreign grains were obtained by drying the grain using a dryer for 12 hours. The novelty of this research is the finding of the right unhulled rice drying time using a dryer